Lavender Oil: A Versatile Natural Therapeutic – Extraction, Composition, Applications, and Innovative Formulation Strategies - Shaikh, Farooque; Harde, Manoj; Mallya, Rashmi (Natural Products Journal, The, 2026)
The present review comprehensively explores an overview of a versatile essential oil from genus Lavandula. Oil finds wide application in the aromatherapy and cosmetic industry. This paper emphasizes the chemical constituents of the oil that are responsible for the diverse therapeutic applications. Various extraction techniques, such as steam distillation, hydro distillation, supercritical liquid extraction and ultrasound assisted extraction are discussed. Also the article elucidates the mechanism of action that explains the therapeutic application of the oil in microbial infections, oxidative stress and neurodegenerative diseases. This review also extensively discusses the preclinical and clinical studies of the use of the oil for the management or treatment of psoriasis, depression, wound, anxiety, Alzheimer’s disease, myocardial infarction, acute lung injury and acute inflammation. Additionally, the article highlights granted patents and the novel formulation strategies such as hydrogels, nanofibers, emulsions and nanoparticles used to enhance the bioavailability and the targeted delivery of the oil. The review also provides future perspectives, emphasizing the need for further research for harnessing the potential of lavender oil.
Keywords: therapeutic application